Development and validation of the Oxford Pandemic Attitude Scale-COVID-19 (OPAS-C): an internet-based cross-sectional study in the UK and USA - Bella Nichole Kantor; Jonathan Kantor (BMJ Open)
Objectives To develop and validate the Oxford Pandemic Attitude Scale-COVID-19 (OPAS-C), a multidimensional scale that addresses seven domains over 20 items including stress, fear, loneliness, sense of community, belief that the pandemic is a hoax or exaggerated, the use of and attitude to non-pharmaceutical interventions and vaccine hesitancy, in a single measure.Design Cross-sectional validation study.Setting Internet based with respondents in the USA and UK.Participants General community respondents using the Prolific Academic platform.Main outcome measures Exploratory factor analyses with promax oblique rotation and confirmatory factor analysis including goodness of fit indices: root mean square error of approximation (RMSEA), standardised root mean square residual (SRMR) and comparative fit index (CFI). Reliability as internal consistency using Cronbach’s alpha. Convergent and discriminant validity using Pearson correlation coefficients.Results The sample included 351 respondents in the USA and the factorial structure was confirmed using a separate set of 348 respondents in the UK. The OPAS-C had excellent goodness of fit characteristics, with an RMSEA of 0.047 (90% CI 0.037 to 0.056), SRMR of 0.043 and CFI of 0.962. Reliability was excellent, demonstrating Cronbach’s alpha of 0.87 in both the US and UK samples. Convergent validity showed correlation coefficients of 0.54 and 0.49 in the US and UK samples, respectively. Discriminant validity demonstrated correlations of 0.21 and 0.26 in the US and UK samples, respectively.Conclusions The OPAS-C represents the first validated scale that addresses mental health measures and public health-relevant responses to COVID-19, and may be a useful measure for use in future longitudinal and cross-sectional studies. Further international validation beyond the USA and UK may be helpful.